Aerial Innovation in Field Triage: Development of the Drone-Integrated Mass Casualty Triage Algorithm (DIMaCTA) - Tayfur, Ismail; Gunduz, Abdulkadir; Simsek, Perihan; Bayramoglu, Burcu; Bal, Mert; Ustubioglu, Arda; Kako, Mayumi; Garner, Shelby; Ryan, Benjamin; Altinarik, Selim; Akgul, Emine Cansu (TAYLOR & FRANCIS INC, 2026)
Object & imath;vesRecently, the rising frequency and severity of mass casualty incidents further complicate the inherently challenging process of mass casualty triage, revealing the need for remote triage. Accordingly, drone-based triage systems are emerging as an innovative solution, supported by advances in image processing technology and remote photoplethysmography for hemodynamic monitoring. Despite these advances, there is limited scientific research regarding algorithms specifically designed for drone-assisted triage. The aim of this study is to develop the Drone Integrated Mass Casualty Triage Algorithm (DIMaCTA).MethodsThe study was conducted in two stages. In the first stage, a draft algorithm was developed using a comprehensive literature review and disaster field experiences. In the second stage, a two-round modified Delphi study was conducted with the participation of emergency medicine specialists to ensure the validity of the algorithm decision points and evaluation criteria. Content validity ratio (CVR) and content validity index (CVI) were calculated to determine the level of expert consensus and content validity. In addition, participants' opinions on the drone-assisted triage application were collected through a researcher-made questionnaire.ResultsThe majority of participants (86.7%) found the drone-based application of the algorithm effective for continuous triage and time-saving in hard-to-reach incidents. In the first Delphi round, more than 80% consensus was reached on the parameters and decision points of the algorithm. Suggestions for pulse and body temperature thresholds were also made in this round. In the second round, the experts agreed on a pulse threshold of 30/min to discriminate between the 'emergency' and 'dead' categories, and a temperature threshold of 28 degrees C for the same classification. In addition, a pulse threshold of 100/minute was agreed to distinguish between 'immediate' and 'delayed' cases. Content validity ratio and CVI values were found to be in the range of 0.73-1.00 and 0.87-1.00, respectively.Conclusions The DIMaCTA is a drone-assisted triage algorithm based on image processing technology and can also be used as a primary triage tool in the field. Its drone-based application is expected to accelerate the prioritization of the most critical cases. Further research is needed to validate the algorithm and assess its potential impact on mass casualty management.
Keywords: CONSENSUS; VALIDITY; SYSTEM; Emergency Medicine; Public, Environmental & Occupational Health